-18⋅(8c-24)+10c=-15

Simplify each term.

Apply the distributive property.

-18(8c)-18⋅-24+10c=-15

Cancel the common factor of 8.

Move the leading negative in -18 into the numerator.

-18(8c)-18⋅-24+10c=-15

Factor 8 out of 8c.

-18(8(c))-18⋅-24+10c=-15

Cancel the common factor.

-18(8c)-18⋅-24+10c=-15

Rewrite the expression.

-1c-18⋅-24+10c=-15

-1c-18⋅-24+10c=-15

Cancel the common factor of 8.

Move the leading negative in -18 into the numerator.

-1c+-18⋅-24+10c=-15

Factor 8 out of -24.

-1c+-18⋅(8(-3))+10c=-15

Cancel the common factor.

-1c+-18⋅(8⋅-3)+10c=-15

Rewrite the expression.

-1c-1⋅-3+10c=-15

-1c-1⋅-3+10c=-15

Multiply -1 by -3.

-1c+3+10c=-15

Rewrite -1c as -c.

-c+3+10c=-15

-c+3+10c=-15

Add -c and 10c.

9c+3=-15

9c+3=-15

Subtract 3 from both sides of the equation.

9c=-15-3

Subtract 3 from -15.

9c=-18

9c=-18

Divide each term in 9c=-18 by 9.

9c9=-189

Cancel the common factor of 9.

Cancel the common factor.

9c9=-189

Divide c by 1.

c=-189

c=-189

Divide -18 by 9.

c=-2

c=-2

Solve for c -1/8*(8c-24)+10c=-15